2008
DOI: 10.1007/s00436-008-0990-8
|View full text |Cite
|
Sign up to set email alerts
|

Infection of red foxes (Vulpes vulpes) with Echinococcus multilocularis during the years 2001–2004 in Poland

Abstract: During the period of 2001-2004, 1,514 red foxes from the north and the southeast of Poland were sampled and examined parasitologically for infections with Echinococcus multilocularis. A mean 23.8% were found infected in the whole study area. The highest prevalence (50.0-62.9%) was found in some counties in the northeastern (Warmia-Mazuria) and the southeastern (Carpathian Foothill) part of the country. During the study period, significant differences in the prevalence were found on a regional level. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 7 publications
2
18
0
2
Order By: Relevance
“…Red foxes (Vulpes vulpes) and raccoon dogs (Nyctereutes procyonoides) can be the final hosts of such dangerous zoonotic parasites as Echinococcus multilocularis or Toxocara spp. Most available data concerning red fox parasites focus only on E multilocularis (4,5,11,12,16,17,23) while some also concern other parasites (2,6,22). The recent study in Podlasie Province, the location of the Augustów Primeval Forest, has shown a relatively high prevalence of this parasite in red foxes (34%) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Red foxes (Vulpes vulpes) and raccoon dogs (Nyctereutes procyonoides) can be the final hosts of such dangerous zoonotic parasites as Echinococcus multilocularis or Toxocara spp. Most available data concerning red fox parasites focus only on E multilocularis (4,5,11,12,16,17,23) while some also concern other parasites (2,6,22). The recent study in Podlasie Province, the location of the Augustów Primeval Forest, has shown a relatively high prevalence of this parasite in red foxes (34%) (11).…”
Section: Introductionmentioning
confidence: 99%
“…6.5 (4.1-9.0) 2 (Jonas & Hahn, 1984;Jonas & Dräger, 1998) 33.8 (-) 1 (Jonas & Dräger, 1998) Saarland 25.6 (19.9-31.3) 2 (Ahlmann, 1996, Meine & Müller, 1996 No data Enge, 1996) No data Schleswig-Holstein 0.2 (0.0-0.4) 3 (Lucius et al, 1988;Nebel, 1996) 0.0 (-) 1 (Manke & Stoye, 1998) (Soldati et al, 1976;Rossi et al, 1983 ;Poglayen et al, 1985 ;Leoni et al, 1986;Iori et al, 1990 ;Guberti & Poglayen, 1991) 0.0 (0.0-0.0) 3 (Di Cerbo et al, 2008;Calderini et al, 2009;Magi et al, 2009) (Ahlmann, 1996;EFSA, 2006;EFSA, 2007;EFSA, 2013a; EFSA, 2015a) Netherlands 0.0 (-) 1 (Borgsteede, 1984) 9.4 (0.7-59.5) 3 (Takumi et al, 2008;Van der Giessen et al, 2004;Van der Giessen et al, 1998;Franssen et al, 2014;Maas et al, 2014) Poland 2.6 (-) 1 (Malczewski et al, 1999) (data until 1998) 15.1 (1.0-20.1) 8 (Borecka et al, 2008;Karamon et al, 2008;Karamon et al, 2011;Borecka et al, 2007;Malczewski et al, 2008;Borecka et al, 2009;Pacon et al, 2006;Karamon et al, 2014 (Ewald & Eckert, 1993;Alther, 1996) 48.5 (44.3-52.7) 2 (Hofer et al, 2000;…”
Section: Countrymentioning
confidence: 99%
“…Ukraine (Kharchenko et al, 2008), Slovakia (Miterpáková et al, 2006), Poland (Malczewski et al, 2008), the Netherlands (Giessen et al, 1999;Borgsteede et al, 2003 ), Germany (Friedland et al, 1985), France (Houin et al, 1982), Switzerland (Hofer et al, 2000;Stieger et al, 2002), Belarus (Merkusheva & Bobkova, 1981;Shimalov & Shimalov, 2003), Russia (Key..., 1978), Estonia (Moks et al, 2005). Whether the range of E. multilocularis, as recognized today, is the result of an expansion or more intensive investigations is not known because of the lack of historical data.…”
Section: Discussionmentioning
confidence: 98%